Seed Coat Pattern QTL and Development in Cowpea (Vigna unguiculata [L.] Walp.) - Herniter, Ira A.; Lo, Ryan; Muñoz-Amatriaín, María; Lo, Sassoum; Guo, Yi-Ning; Huynh, Bao-Lam; Lucas, Mitchell; Jia, Zhenyu; Roberts, Philip A.; Lonardi, Stefano; Close, Timothy J. (Frontiers in Plant Science, 2019)
The appearance of the seed is an important aspect of consumer preference for cowpea (Vigna unguiculata [L.] Walp.). Seed coat pattern in cowpea has been a subject of study for over a century. This study makes use of newly available resources, including mapping populations, a reference genome and additional genome assemblies, and a high-density single nucleotide polymorphism genotyping platform, to map various seed coat pattern traits to three loci, concurrent with the Color Factor (C), Watson (W), and Holstein (H) factors identified previously. Several gene models encoding proteins involved in regulating the later stages of the flavonoid biosynthesis pathway have been identified as candidate genes, including a basic helix-loop-helix gene (Vigun07g110700) for the C locus, a WD-repeat gene (Vigun09g139900) for the W locus and an E3 ubiquitin ligase gene (Vigun10g163900) for the H locus. A model of seed coat development, consisting of six distinct stages, is described to explain some of the observed pattern phenotypes.